Talking: Talking Shops - Blake Lee-Whiting; Lewis Krashinsky; William Roelofs (Institute for Replication (I4R), 2023)
In Talking Shops: The Effects of Caucus Discussion on Policy Coalitions, Zelizer analyzes the causal effect of caucus deliberations on legislative policy coalitions. In practice, political scientists have little empirical evidence on how policy discussions actually work among sitting legislators and whether these discussions have an effect on policy making and policy opinion. Taking on this challenge, Zelizer conducted two field experiments in an American state legislature. In short, the experiments randomized whether a bill was selected for discussion among a bi-partisan legislative caucus. The paper then measures and reports the corresponding effects of that discussion around the bill. Zelizer finds that deliberation increased the amount of co-sponsorship for a given bill, among both co-partisans and counter-partisans, but deliberation did not effect whether a bill was passed by the legislature or whether the bill received more amendments. We conduct a robustness replication of the main results of Talking Shops. Specifically, we reproduce Tables 3 and 4 of the paper under alternative specifications. We find that the main results of the paper are reproducible and robust to multiple alternative specifications.
Keywords: 330